Students' Consideration of Choosing Nursing Career for the Future - Wardhani, Utari; Muharni, Sri; Louisa De Marillac Nogo Niron (Caring: Indonesian Journal of Nursing Science, 2025)
Nursing is a profession that demands responsibility, empathy, and sustained commitment. Despite its critical role in healthcare systems, the profession is currently facing significant global challenges, most notably a widespread shortage of nursing personnel. This shortage is further exacerbated by a declining interest among younger generations in selecting nursing as a career, raising concerns about the future sustainability of the healthcare workforce. Therefore, this study aims to explore students' considerations when choosing nursing as a future career in a private school in Batam. A qualitative phenomenological approach was used, and data were collected through semi-structured interviews recorded using a Digital Voice Recorder. A total of 15 participants were selected based on data saturation. Four key themes were identified, including Nursing as a Noble Profession, Nurses as Role Models, Support for Becoming a Nurse, and Challenges in Choosing a Nursing Career. Students often perceive the nursing profession as noble and dignified, largely due to its dedication to caring for and helping others. The experience of being cared for and seeing nurses doing their job became students' role models in the future. Another factor was that social support was found to encourage students to pursue nursing. On the other hand, barriers such as gender stigma, the high cost of nursing education, and family economic difficulties are significant challenges in choosing this career. In conclusion, students' decisions to choose nursing are influenced by both supportive and obstructive factors. This study suggests that further investigation should be conducted using nursing theory, focusing on how clinical experiences during nursing education impact students' career goals in the context of personal, interpersonal, and social systems. Understanding these dynamics could help improve the recruitment and retention of nursing students.